Breaking Down “Firewall“ among Public Relations and Journalism - Jamroji Jamroji; Nasrullah Nasrullah (UMSU, 2020)
Public Relations (PR) and journalism are often disputed in theory and practice. While PR is an activity that aims to improve goodwill, trust, mutual understanding and a good image of the community or society, in the other hand journalism has a social responsibility to provide accurate information for the community through the media. The increase of communication technology has been changing business media and also affected the PR strategy in Indonesia that bring together PR and journalism as one of campaign strategies. The boundary between PR and journalism does not exist anymore. The firewall concept that separates roles of journalism, advertising, and PR now is blurred. Paid microsites, advertorials, and Media Relations practices such as press tours, press releases, press gatherings, led to the emergence of journalistic work with a ‘smooth’ PR approaches to increase the image of the person and institution. It can’t call journalism, because it leads interests that the public does not necessarily want, despite using journalism rules in coverage.